Algorithm of the effect of g-jittren on free convection adjacent to a stretching sheet - Shafie, Sharidan (Faculty of Science, 2009)
g-Jitter characterizes a small fluctuating gravitational field brought about, among others, by crew movements and machine vibrations aboard spacecrafts or in other low-gravity environments such as the drop-tower and parabolic flights. Experimental studies have shown that in these low-gravity environments, g-jitter can induce appreciable convective flow that can be detrimental to certain experiments such as crystal growths and solidification processes. In this research, mathematical models to study the effect of g-jitter on heat and mass transfer is developed. Specific problem considered revolve around the effect of g-jitter induced free convection, on the flow and heat transfer characteristics associated with a stretching vertical surface in a viscous and incompressible fluid. The velocity and temperature of the sheet are assumed to vary linearly with x, where x is the distance along the sheet. It is assumed that the gravity vector modulation is given by g *(t) = go [1+Îµ cos (Ï€ Ï‰ t)]k , and the resulting non-similar boundary layer equations are solved numerically using an implicit finite-difference scheme. Results presented include fluid flow and heat transfer characteristics for various parametric physical conditions such as the amplitude of modulation, frequency of the single-harmonic component of oscillation, buoyancy force parameter and Prandtl number on the skin friction and Nusselt number. This theoretical investigation is useful in providing estimates of the tolerable effects of g-jitter which will help to ensure the design of successful experiments in low-gravity environments.